The Communist manifesto - Marx, Karl, 1818-1883; Engels, Friedrich, 1820-1895 (Rethinking the Western tradition., 2012)
Contains the "Communist Manifesto," several essays discussing the historical background of the manifesto and its influence today, all of the prefaces to the manifesto used during Marx and Engels' lifetime, and Engels' "Principles of Communism."